Evaluasi Kebijakan Penataan Pkl Oleh Pemerintah Kota Surakarta di Kecamatan Laweyan Kota Surakarta - Eko Purnomo; Yitno Puguh Martomo (Syntax Corporation Indonesia, 2024)
The objectives of this study are: (1) to find out the policy of the Surakarta City Government in organizing street vendors in Laweyan, (2) to find out the extent of the Surakarta City Government's policy in improving the welfare of street vendors. The approach used in this study is a qualitative approach. The research location is in Laweyan, Trade Office in the field of PKL Management and Satpol PP Surakarta City. The focus of this research is the policy of the Surakarta City Government in organizing street vendors in Laweyan, the extent of the Surakarta City Government's policy in improving the welfare of street vendors. The primary data sources in this study are street vendors in Laweyan, officers of the Trade Office of the PKL Management section, officers of Satpol PP Surakarta City. The results showed that to overcome the problem of mushrooming street vendors, the Surakarta City Government issued Regional Regulation Number 3 of 2008. In its implementation, the Regional Regulation is assisted by the existence of Guardian Number 17B of 2012 and also Mayor Decree Number 510 of 2012. The policy issued by the Surakarta City Government empowers street vendors in the form of providing cart assistance, capital assistance, counseling and also cart and umbrella assistance.